Timing of Umbilical Cord Separation and Neonatal Intensive Care Unit Practices - Aygün, C.; Subaşi, A.; Küçüködük, Ş. (Thieme Medical Publishing Inc, 2005)
We investigated the effects of antibiotic and corticosteroid treatment of the mother close to birth and postnatal neonatal intensive care unit (NICU) practices such as phototherapy, parenteral nutrition, and antibiotic treatment of the infant on umbilical cord detachment time. The impact of dry cord care on risk of omphalitis in NICU patients was also investigated. Cord separation time was longer in preterm babies. Antenatal antibiotic and corticosteroid use did not affect cord detachment time. The use of postpartum antibiotics, parenteral nutrition, and phototherapy delayed cord separation. Among these, antibiotic treatment was the most effective factor. Dry cord care did not increase the risk of omphalitis in NICU patients in our series. Copyright © 2005 by Thieme Medical Publishers, Inc.
Keywords: Affecting Factors; Separation; Umbilical Cord